2005
DOI: 10.1021/ol0501828
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 2- and 4-Arylmethyl N-Substituted and N,N-Disubstituted Anilines via a “Green”, Multicomponent Reaction

Abstract: [reaction: see text] A new, green, regioselective, one-step, multicomponent reaction of an aldehyde possessing a nonenolizable carbonyl function, cyclohex-2-enone (or a derivative thereof), and primary or secondary amines afforded 2-N-substituted arylmethyl anilines or 4-N,N-disubstituted arylmethyl anilines, respectively. Yields and regioselectivities were good. Evidence for a pathway involving imine and iminium intermediates is presented along with examples demonstrating amenability of the process to combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This is further supported by the 13 C NMR spectrum, which contains two peaks at δ = 38.4 and 47.7 indicating the two types of benzylic carbons. The NMR data of known compound 4ab were also in good correlation with previously reported data [ 19 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This is further supported by the 13 C NMR spectrum, which contains two peaks at δ = 38.4 and 47.7 indicating the two types of benzylic carbons. The NMR data of known compound 4ab were also in good correlation with previously reported data [ 19 ].…”
Section: Resultssupporting
confidence: 87%
“…The Semmler–Wolff reaction is often implemented in the synthesis of anilines through Brønsted acid or transition-metal-promoted conversion of 2-cyclohexanone oximes [ 15 18 ] ( Scheme 1 , (2)). Moreover, Strauss and co-workers described a green, multicomponent reaction of aromatic aldehydes, 2-cyclohexenone and amines to afford 2-arylmethyl N -substituted anilines [ 19 ] ( Scheme 1 , (3)). To date, although plentiful amination–aromatization approaches for the preparation of anilines have been well-established, to develop novel and efficient synthetic methods still remains highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization afforded a general one-step multi-component preparation of N-monosubstituted or N,N-disubstituted aniline derivatives. [101] The reactants comprise an aldehyde without an enolizable carbonyl function, cyclohex-2-enone or a derivative thereof and an amine, which may be primary or secondary. The simplest cases involve monoaldehydes and monoamines (see Scheme 11 for examples featuring benzaldehyde with primary or secondary amines).…”
Section: Cascade Reaction For Aniline Derivativesmentioning
confidence: 99%
“…di-(2-methoxyethyl)amine, morpholine, amphetamine, and di-n-butylamine. [101] Potential Impacts of Deep-Sea Disposal of CO 2 Not all environmental implications of chemicals result from chemical laboratories or chemical manufacturing. Perhaps the most topical example concerns the effects of increasing atmospheric concentrations of greenhouse gases such as CO 2 and CH 4 on climate.…”
Section: Cascade Reaction For Aniline Derivativesmentioning
confidence: 99%
“…In recent investigations into the generation of aromatic species from masked precursors, 1 we discovered a green, multicomponent cascade reaction for the preparation of 2-and 4-arylmethyl N-substituted and N,N-disubstituted anilines. 2 Several known product anilines have pre-existing industrial applications and some of our new compounds have shown interesting biological activities. 3 Consequently, we have extended the scope of our studies into aromatisation to include substituted phenylenediamines such as N,N9-dialkylp-phenylenediamines (1).…”
Section: Introductionmentioning
confidence: 99%